ANALISIS KINERJA PEGAWAI BERDASARKAN FAKTOR SDM, KEDISIPLINAN DAN BUDAYA ORGANISASI PADA LAPAS KELAS IIB BIREUEN - Masri, Masri; Zainuddin; Mai (IndOmera, 2024)
Performance-based work assessment for civil servants must guarantee the objectivity of civil servant development based on achievement systems and career systems. Assessments are carried out based on performance planning at the individual and unit or organizational level, taking into account targets, achievements, results, benefits achieved and behavior, in accordance with PP No. 20 of 2019. Of course there are many personal factors that will influence. contribute to employees, such as the quality of resources. Humane, supported by high work discipline. Apart from that, sometimes there are also drivers who are very close to the work and environment, implementing a work culture in the organization in accordance with applicable regulations. This is the focus of this research. With research on 57 Class IIB Bireuen Correctional Institution (LAPAS) employees. This research takes the form of a survey using questionnaires and data analysis techniques with a descriptive approach and statistical analysis using the path analysis model. The research results found that (a) there was a direct and indirect influence of HR factors, work discipline and organizational culture on performance of 31.09%, 15.51% and 16.85% respectively. (b) simultaneously these three factors make a positive contribution to employee performance by 59%.